2018
DOI: 10.1038/s41598-018-30665-6
|View full text |Cite
|
Sign up to set email alerts
|

A direct interaction between two Restless Legs Syndrome predisposing genes: MEIS1 and SKOR1

Abstract: Restless Legs syndrome (RLS) is a common sleep disorder for which the genetic contribution remains poorly explained. In 2007, the first large scale genome wide association study (GWAS) identified three genomic regions associated with RLS. MEIS1, BTBD9 and MAP2K5/SKOR1 are the only known genes located within these loci and their association with RLS was subsequently confirmed in a number of follow up GWAS. Following this finding, our group reported the MEIS1 risk haplotype to be associated with its decreased ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 42 publications
3
23
0
1
Order By: Relevance
“…Consistent with previous findings 9 , 10 , expression of three previous RLS GWAS genes, MEIS1 in the dorsolateral prefrontal cortex and tibial nerve, SKOR1 in frontal cortex and pituitary, and MAP2K5 in the dorsolateral prefrontal cortex were associated with RLS. Two additional genes, IQCH and SKAP1 , which were not reported in the previous GWAS, were significantly associated with the RLS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous findings 9 , 10 , expression of three previous RLS GWAS genes, MEIS1 in the dorsolateral prefrontal cortex and tibial nerve, SKOR1 in frontal cortex and pituitary, and MAP2K5 in the dorsolateral prefrontal cortex were associated with RLS. Two additional genes, IQCH and SKAP1 , which were not reported in the previous GWAS, were significantly associated with the RLS.…”
Section: Discussionsupporting
confidence: 92%
“…In the previous RLS GWAS, MEIS1 was identified as the most significant genetic risk factor, motivating subsequent functional studies of this gene 9 , 10 . However, fine-mapping of the corresponding genomic locus prioritized PPP3R1 with a posterior probability of 0.63 in the 90%-credible gene set.…”
Section: Discussionmentioning
confidence: 99%
“…Expression studies of the RLS associated loci of BTBD9, MAP2K5 , and SKOR1 (previously called LBXCOR1 ) did not find changes in their levels of expression in lymphoblasts or two brain regions (pons and thalamus) of RLS patients (43). However, RLS patients with the MEIS1 risk haplotype were observed to have a reduced expression of SKOR1 , in addition to a reduced expression of MEIS1 (Figure 1) (43). Follow up studies using siRNA targeting MEIS1 , electromobility shift assays and luciferase reporter assays suggested the expression of SKOR1 to be under the regulatory control of MEIS1.…”
Section: Meis1 Regulates Skor1mentioning
confidence: 95%
“…Follow up studies using siRNA targeting MEIS1 , electromobility shift assays and luciferase reporter assays suggested the expression of SKOR1 to be under the regulatory control of MEIS1. This transcription factor action of MEIS1 is due to its direct binding on two distinct promoter regions of SKOR1 (43). Hence the dysregulation of MEIS1 might predispose to RLS both directly and indirectly, possibly throughout its regulatory role on other genes like SKOR1 .…”
Section: Meis1 Regulates Skor1mentioning
confidence: 99%
“…76 The link between MEIS1and SKOR1 was further elucidated by Catoire et al potentially implicating them in the modulation of pain and sensory input processing of RLS. 77 Interestingly, one study on childhood-onset RLS showed the association with MEIS1 and what is currently referred to as SKOR1, but not with BTBD9. 61 Iron deficiency has been the single best documented biological abnormality for RLS.…”
Section: Genetics and Pathophysiologymentioning
confidence: 99%